Youth pre-pandemic executive function relates to year one COVID-19 difficulties - Aizza, Alice; Porter, Blaire M.; Church, Jessica A. (Frontiers in Psychology, 2023)
The COVID-19 pandemic presents a series of stressors that could relate to psychological difficulties in children and adolescents. Executive functioning (EF) supports goal achievement and is associated with life success, and better outcomes following early life adversity. EF is also strongly related to processing speed, another predictor of life outcomes. This longitudinal study examined 149 youths’ pre-pandemic EF and processing speed abilities as predictors of self-reported emotional, cognitive, and social experiences during two timepoints of the first year of the COVID-19 pandemic. Better pre-pandemic EF skills, and processing speed abilities predicted more mid-COVID-19 (January-March of 2021) pandemic emotional and cognitive difficulties. On the other hand, better switching (a subcomponent of EF) and processing speed abilities predicted more mid-pandemic social interactions. EF and processing speed abilities did not relate to the reports from the initial months of the pandemic. Our EF - but not processing speed - results were largely maintained when controlling for pre-pandemic mental health burden, socioeconomic status (SES), and gender. Better cognitive abilities may have contributed to worse pandemic functioning by supporting the meta-cognition needed for attending to the chaotic and changing pandemic news, leading to higher stress-induced worry and rumination.